Design optimization of shell and tube type heat exchanger of G.A Siwabessy multi-purpose reactor cooling system - Gaos, Yogi Sirodz; Nurtanto, Bagus Dwi; Al Kindi, Hablinur; Sutoyo, Edi (Jurnal Polimesin, 2024)
G.A Siwabessy multi-purpose reactor is a nuclear reactor that utilizes a controlled fission reaction (a chain reaction of atomic fission). The heat exchanger in the reactor cooling system plays a vital role in transfering heat from the primary coolant side to the secondary coolant side. Heat transfer coefficient (U) and heat transfer area (Ao) are two variables that have a huge influence on the success of heat transfer in a heat exchanger. The aim of this research is to compare the U and A values in two different ways, namely the full factorial method and the use of Heat Transfer Research Inc. (HTRI) software. The novelty of this research is the use of two different methods to check the U and A0 values of heat exchangers in nuclear reactors. In the calculation using the full factorial method, 4 independent variables with 3 levels were made, so 81 calculations were obtained. The most optimal calculation results are then validated with HTRI software. From the calculation results, it is known that the largest overall heat transfer coefficient (U) is 6531.60 W/m2 °C with a heat transfer area (Ao) of 584.47 m2 . The results of the validation with the HTRI software obtained an overall heat transfer coefficient (U) of 5045.10 W/m2 °C with a heat transfer area (Ao) of 574.19 m2 . There is a difference in value between the results of manual calculations and the results of the validations of the HTRI software which is made possible by a decrease in the performance of the heat exchanger.